Pengaruh Metode RGEC Terhadap Pertumbuhan Laba Pada Perbankan Milik Negara Yang Terdaftar Di Bursa Efek Indonesia - Widarti Widarti; Niska Wulandari (UNIVED Press, 2022)
This study aims to determine the Effect of Variable Risk Profile as measured by Non-Performing Loans (NPL) and Loan to Deposit Ratio (LDR), Good Corporate Governance as measured by Operational Costs and Operating Income (BOPO), Earnings as measured by Return On Assets ( ROA), Capital as measured by Capital Adequacy Ratio (CAR) to Profit Growth. This study uses secondary data obtained from the annual financial statements of banking companies listed on the Indonesia Stock Exchange (IDX) in 2013-2017 accessed from the website www.idx.co.id. The population in this study were state-owned banks, while the samples used in the study were taken from all populations, there were 4 samples. using saturated sampling techniques, all populations are used as samples, namely BUMN banks listed on the Stock Exchange, including PT. Bank Mandiri (Persero), PT. Bank Negara Indonesia (Persero), PT. Bank Rakyat Indonesia (Persero), PT. State Savings Bank (Persero). Based on the results of testing the Hypothesis, simultaneously (Test F) the results obtained that Independent Variables NPL, LDR, BOPO, ROA, and CAR together do not affect earnings growth. Whereas partially (T Test) Independent Variables of NPL and BOPO have negative and not significant effect on earnings growth followed by Independent Variables LDR, ROA, and CAR have a positive effect not significant on profit growth.